Baseline and Clinical Factors Associated with Response to Amblyopia Treatment in a Randomized Clinical Trial. Issue 5 (May 2020) - Birch, Eileen E.; Jost, Reed M.; Kelly, Krista R.; Leffler, Joel N.; Dao, Lori; Beauchamp, Cynthia L.
Abstract : SIGNIFICANCE: We sought to identify baseline and clinical factors that were predictive of the response to amblyopia treatment. We report that binocular amblyopia treatment may be especially effective for moderate amblyopia in orthotropic children. PURPOSE: We previously reported results from the primary cohort (n = 28) enrolled in a randomized clinical trial (NCT02365090), which found that binocular amblyopia treatment was more effective than patching. Enrollment of an additional 20 children was pre-planned to provide the opportunity to examine factors that may be predictive of response to amblyopia treatment. METHODS: Forty-eight children (4 to 10 years old) were enrolled, with 24 randomized to contrast-rebalanced binocular game treatment (1 hour a day, 5 days a week) and 24 to patching treatment (2 hours a day, 7 days a week). The primary outcome was change in amblyopic eye best-corrected visual acuity at the 2-week visit. Baseline factors examined were age at enrollment, visual acuity, stereoacuity, and suppression. Clinical factors were etiology, age at diagnosis, prior treatment, and ocular alignment. RESULTS: At 2 weeks, visual acuity improvement was significantly greater with the binocular game than patching. Children with moderate amblyopia and orthotropia had more visual acuity improvement with binocular game play than did those with severe amblyopia. In addition, children who spent more time playing the binocular game had more improvement. We were not able to confidently identify any baseline or clinical factors that were associated with response to patching treatment. CONCLUSIONS: Binocular amblyopia treatment was more effective among orthotropic children with moderate amblyopia than among children with microtropia or severe amblyopia. Abstract : Supplemental digital content is available in the text.